2011
DOI: 10.1152/ajpgi.00462.2010
|View full text |Cite
|
Sign up to set email alerts
|

Lactose maldigestion during methotrexate-induced gastrointestinal mucositis in a rat model

Abstract: Fijlstra M, Rings EH, Verkade HJ, van Dijk TH, Kamps WA, Tissing WJ. Lactose maldigestion during methotrexate-induced gastrointestinal mucositis in a rat model. Am J Physiol Gastrointest Liver Physiol 300: G283-G291, 2011. First published November 18, 2010 doi:10.1152/ajpgi.00462.2010.-Patients with chemotherapy-induced gastrointestinal mucositis suffer from anorexia, diarrhea, and stomach pain, often causing weight loss and malnutrition. When the intestinal function during mucositis would be known, a rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 42 publications
3
43
0
1
Order By: Relevance
“…The ingestion of a HLD resulted in the onset of diarrhea in less than 24 h. The signs of diarrhea and loss of body weight seen in this study correspond with findings from previous studies in which rats fed HLD had chronic diarrhea and became malnourished (Arciniegas et al, 2000;Bueno et al, 1994;Fijlstra et al, 2010;Lawrence et al, 1956;Liuzzi et al,1998;Norton et al, 2001). Few animals with delayed onset diarrhea consumed less food indicating a correlation of disease severity with the amount of diet consumed.…”
Section: Garcinia Buchananii Bark Extract Treats Lactose-induced Diarsupporting
confidence: 88%
See 2 more Smart Citations
“…The ingestion of a HLD resulted in the onset of diarrhea in less than 24 h. The signs of diarrhea and loss of body weight seen in this study correspond with findings from previous studies in which rats fed HLD had chronic diarrhea and became malnourished (Arciniegas et al, 2000;Bueno et al, 1994;Fijlstra et al, 2010;Lawrence et al, 1956;Liuzzi et al,1998;Norton et al, 2001). Few animals with delayed onset diarrhea consumed less food indicating a correlation of disease severity with the amount of diet consumed.…”
Section: Garcinia Buchananii Bark Extract Treats Lactose-induced Diarsupporting
confidence: 88%
“…The considerable decrease in the weight of HLD rats indicates malnutrition (Bueno et al, 1994;Fijlstra et al, 2010;Liuzzi et al, 1998;Norton et al, 2001), which is a key symptom of lactoseinduced diarrhea in humans (Brown, 2003;Lomer et al, 2008;Moore et al, 2010;Nyeko et al, 2010). In most incidences of diarrhea, intestinal injury, altered mucosal function and loss of appetite results in poor nutritional status (Brown, 2003;Moore et al, 2010;Nyeko et al, 2010;Thapar and Sanderson, 2004;UNICEF/WHO, 2009).…”
Section: Lower Doses and Anti-motility Fractions Of G Buchananii Barmentioning
confidence: 99%
See 1 more Smart Citation
“…CON, control group of rats fed control diet; MTX, methotrexate-administration group of rats fed control diet; MTX-ERF, methotrexate-administration group of rats fed diet containing extract of fermented brown rice The mucosal weight was also significantly decreased, and pathological scores of the intestines were significantly increased by the administration of MTX, as shown in Table 4 and Table 6. Fijlstra et al 23) have suggested that the administration of MTX decreased the activity of glycohydrolases, crucial enzymes related to carbohydrate digestion and glucose absorption, resulting in diarrhea. These findings agree with our results, at least in part.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical studies, it was shown that plasma citrulline correlates significantly with the villus length in a methotrexate-induced mucositis rat model [23]. Furthermore, preclinical studies showed that the use of plasma citrulline corresponded with radiation-induced mucositis in rats and mice [24, 25].…”
Section: Potential Biomarkers In Blood Samplesmentioning
confidence: 99%